SEPTOPLASTY IN CHILDHOOD: FROM DIAGNOSIS TO TREATMENT - Beppu , Paula Mortoza Lacerda; Sgarbi, Francisco de Arruda; Vergaças , Matheus Sgarbi; Tanuri , Giovanna Emanuella Piffer (Seven Editora, 2024)
Septoplasty in children aims to correct deviations in the nasal septum that compromise breathing and quality of life. This study is a narrative review that analyzes the available approaches for pediatric septoplasty, considering surgical techniques and the use of bone and cartilaginous grafts. The search was carried out in the PUBMED, LILACS and SCIELO databases, and the inclusion and exclusion criteria were rigorously applied. The results indicate the importance of an individualized and careful approach in the choice of procedures, ensuring aesthetic and functional improvement in pediatric patients. It is concluded that septoplasty in children can bring significant benefits when well indicated and planned. DOI:https://doi.org/10.56238/sevened2024.039-003